Relative age effect and the re-selection of Danish male handball players for national teams - Wrang, C. M.; Rossing, N. N.; Dierncs, R. M.; Hansen, C. G.; Dalgaard-Hansen, C.; Karbing, D. S. (Journal of Human Kinetics, 2018)
The relationship between the date of birth and expertise in various sports among both elite and youth level athletes is well established, and known as the relative age effect (RAE). However, new results in for example Canadian Hockey and British cricket and rugby have indicated a reversal of RAE among selected talents where the youngest athletes are more likely to remain selected than their older peers. As such, RAE may therefore depend on the age and the level of competition. The purpose of this study was therefore to analyse RAE from the youth to senior national level in a sample of successful Danish male national teams. The sample included 244 players from Danish under-19, under-21 and senior national levels. These players have been part of successful teams, winning 18 medals at 24 youth European and World championships and 8 medals during 12 years at the senior level. The results showed a significant RAE on both youth and national levels. However, RAE was less marked from the under-19 to under-21 and further to the senior national level. Results show that at the national youth level talent selection favours the relatively older players, of whom a larger proportion fails to be re-selected to the senior level compared to their younger peers. RAE appears to play a central and reversing role in the identification and re-selection in Danish male handball. The results also show that the presence of both a constant and constituent year structure affects RAE, even when introduced at late adolescence.